PERMAINAN EDUKATIF (MISSING LYRICS) DALAM MENINGKATKAN KETERAMPILAN MENDENGAR SANTRI DI MARKAZ ARABIYAH PONDOK PESANTREN AL-QODIRI 1 JEMBER - Priyono, Dwi Juli; Azisi; Elok Rufaiqoh (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2024)
Arabic language learning cannot be separated from efforts to improve the four language skills. There are many ways to enhance students' listening skills, one of which is by using enjoyable educational games. In Arabic language learning, appropriate methods are also required to effectively implement educational games such as "Missing Lyrics." This study focuses on the planning, implementation, and evaluation of using the "Missing Lyrics" educational game to improve the listening skills of students at Markaz Arabiyah, Al-Qodiri 1 Islamic Boarding School, Jember. This research uses a qualitative approach. The technique for selecting informants is purposive sampling. Data collection methods include observation, interviews, and documentation. Data analysis is based on the Miles and Huberman model, which consists of data reduction, data display, and drawing conclusions or verification. The validity of the data is ensured through triangulation. The results of the study show that the "Missing Lyrics" educational game can improve students' listening skills, enrich their vocabulary, and correct their pronunciation. The game also enhances motivation, engagement, as well as students' social and teamwork skills. Furthermore, the use of Arabic songs in the game helps students understand grammar contextually and introduces them to Arabic culture. Keywords: Educational Game, Missing Lyrics, Listening Skills